2008
DOI: 10.1186/1471-2296-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Complementary or alternative? The use of homeopathic products and antibiotics amongst pre-school children

Abstract: Background: Any intervention to reduce the inappropriate use of antibiotics for infections in children has the potential to reduce the selective pressure on antimicrobial resistance and minimise the medicalisation of self-limiting illness. Little is known about whether homeopathic products might be used by some families as an alternative to antibiotics or the characteristics of such families. We used the Avon Longitudinal Study of Parents and Children (ALSPAC) observational dataset to explore the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A sister study within the ALSPAC CAM study group showed no reduction in antibiotic use in homeopathic users. 26 As previously mentioned, observational data suggest a benefit of HP in the management of asthma, and qualitative data reflected parents' desire to take greater personal control over their child's condition and to be less dependent on medication. 27 However, systematic reviews suggest that evidence is insufficient for a clinical benefit of homeopathy in asthma, but also suggest that it is important to investigate homeopathy as a package of care rather than homeopathy as a single intervention.…”
Section: Discussionmentioning
confidence: 92%
“…A sister study within the ALSPAC CAM study group showed no reduction in antibiotic use in homeopathic users. 26 As previously mentioned, observational data suggest a benefit of HP in the management of asthma, and qualitative data reflected parents' desire to take greater personal control over their child's condition and to be less dependent on medication. 27 However, systematic reviews suggest that evidence is insufficient for a clinical benefit of homeopathy in asthma, but also suggest that it is important to investigate homeopathy as a package of care rather than homeopathy as a single intervention.…”
Section: Discussionmentioning
confidence: 92%
“…10 Globally, personal use of homeopathy in doctors has a strong association with prescribing of homeopathy. 11 There is also some evidence on patient factors associated with choosing homeopathy, again based on surveys: patients are most likely to be female, better educated, have healthier lifestyles and report lower tendency to seek medical help when their child is ill. 12,13 Using publicly available data, practices may be measured on their prescribing quality through assessment of the cost-effectiveness, efficacy and safety of medicines prescribed, based on national guidelines. Practices may also be judged by their quality outcomes framework score and patient recommendation rates.…”
Section: Introductionmentioning
confidence: 99%
“…10 Globally, personal use of homeopathy in doctors has a strong association with prescribing of homeopathy. 11 There is also some evidence on patient factors associated with choosing homeopathy, again based on surveys: patients are most likely to be female, better educated, have healthier lifestyles and report lower tendency to seek medical help when their child is ill. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of psychological disorders include headache, lost appetite, weight loss, and insomnia [9]. In addition, language barriers prevent effective communication with medical staff limit the immigrants’ use of healthcare services, and family members or friends become the major sources of information [7,10]. …”
Section: Introductionmentioning
confidence: 99%